Calibration method for the noninvasive current measurement of multicore cables based on two-step estimation - SONG Xian; ZHANG Yong-jun; NING Bei-fei; WANG Wei (工程科学学报)
The noninvasive measurement of multicore cables using space magnetic field analysis has characteristics of weak signal intensity, high sensitivity, and vulnerability to environmental or elemental interference. To calibrate the hard iron bias, soft iron bias, and scale factor of magnetoresistance sensors based on noninvasive measurements for multicore cables, a two-step estimation-based calibration method was proposed. This method establishes the error-related linear matrix equations through the nonlinear transformation of the sensor output signal and undertakes nonlinear regression calculation after solving the equations, thus implementing dynamic error correction for the measurement of multicore cable current. Results show that this method can simultaneously calibrate linear and partial nonlinear errors of noninvasive current measurement devices for multicore cables.